Synergistic effect of co-culture rhizosphere Streptomyces: A promising strategy to enhance antimicrobial activity and plant growth-promoting function - Li, Jing; Zhang, Lin; Yao, Gan; Zhu, Lixiang; Lin, Jingling; Wang, Chengqiang; Du, Binghai; Ding, Yanqin; Mei, Xiangui (Frontiers in Microbiology, 2022)
Rhizosphere Streptomyces is one of the important types of rhizosphere microorganisms， which plays an important role in promoting plant growth and controlling plant diseases to maintain agricultural ecosystem balance and green ecological agriculture development as beneficial bacteria. Microbial co-culture simulates the complex biocommunity in nature, which has more advantages than the mono-culture with synergistic effect. As the key signal mediums of microorganisms, plants and their interactions, microbial metabolites are of great significance in revealing their functional mechanism. In this study, two potential plant growth-promoting rhizobacteria, Streptomyces albireticuli MDJK11 and Streptomyces alboflavus MDJK44, were selected to explore the effects of co-culture and mono-culture on plant growth promotion and disease prevention, and the metabolic material basis were analyzed by metabonomics. Results showed that Streptomyces MDJK11, MDJK44 mono-culture and co-culture condition all showed good growth promoting and antimicrobial effects. What’s more, compared with the mono-culture, the co-culture showed the advantage of synergistic enhancement effect. LC-MS based metabonomics analysis showed the metabolic material bases of Streptomyces for plant growth promotion and disease prevention were mainly plant hormone and antibiotics and the co-culture condition could significantly stimulate the production of plant hormone promoters and macrolide, cyclic peptide and aminoglycoside antibiotics. The study proved that co-culture of S. albireticuli MDJK11 and S. alboflavus MDJK44 has great potential in crop growth promotion and disease prevention.